Global Outcome and Late Seizures After Penetrating Versus Closed Traumatic Brain Injury: A NIDRR TBI Model Systems Study. Issue 4 (July 2015) - Walker, William C.; Ketchum, James S.; Marwitz, Jennifer H.; Kolakowsky-Hayner, Stephanie A.; McClish, Donna K.; Bushnik, Tamara
Abstract : Background: If and how much dural penetration influences long-term outcome after traumatic brain injury (TBI) is understudied, especially within the civilian population. Objectives: Using the large TBI Model Systems cohort, this study assessed and compared penetrating TBI (PTBI) and closed TBI with respect to global outcome and late seizures 2 years after injury. Methods: After performing unadjusted PTBI versus closed TBI comparisons, multivariate regression models were built and analyzed for both outcomes by including the following additional predictors: length of unconsciousness, posttraumatic amnesia duration, hospital length of stay, age, gender, race, marital status, education level, problem substance abuse, and preinjury employment status. Results: The collapsed Glasgow Outcome Scale model ( n = 6111) showed significant secondary effects of PTBI with employment status. When employed before injury, individuals with PTBI were 2.62 times more likely (95% confidence interval, 1.92-3.57) to have a lower Glasgow Outcome Scale category. The final model for late seizures ( n = 6737) showed a significant main effect for PTBI. Adjusting for other predictors, individuals with PTBI were 2.78 times more likely (95% confidence interval, 1.93-3.99) than those with closed TBI to be rehospitalized for a seizure. Conclusion: This study empirically demonstrates that penetrating injury mechanism has important prognostic implications.